Pengaruh Berbagai Jenis Aplikasi Auksin Dan Bahan Setek Daun Terhadap Pertumbuhan Tanaman Peperomia (Peperomia argyreia) - Aini, Nurul; Isnaeni, Selvy; Rosmala, Arrin (Universitas Wiralodra, 2024)
Peperomia watermelon (Peperomia argyreia) ornamental plant, its existence is still quite rare, due to the long propagation time, so efforts are needed to help the growth of Peperomia plants to be faster. This study aims to determine the growth response of peperomia plant leaf cuttings to various types of auxin application treatments with the leaf cutting materials. This research was conducted at the Screen House of Agrotechnology, Faculty of Agriculture, Universitas Perjuangan Tasikmalaya in January – April 2022. The design used to be a Completely Randomized Design (CRD) with two factors. The first factor giving synthetic auxin application consisted of 4 levels, namely: control, solution, paste, flour, and the second factor was the type of leaf cuttings consisting of 3 levels, namely: intact leaves, half lower part of leaves, half top part of leave (S3). There were 12 treatment combinations, repeat 3 times, each experimental unit consisting of 3 plants so that the total plants were 108 plants. The results of this research show that there is a significantly different interaction between the treatment of the variable percentage of survival and the percentage of cuttings sprouting. Auxin treatment and the type of leaves cuttings each gave a significant effect on the variable length of the root, that is in the treatment of the type of solution application (R1) by showing the longest root value of 6,26 cm and the treatment of the intect leaves (S3) is by showing the root value of 6,49 cm. While the treatment did not give significantly different results for the number of leaves, the number of main roots, root branches, and shoots